Mycotoxins Occurence in Feed and Their Influence on Animal Health - Gajęcki, Maciej; Gajęcka, Magdalena; Zielonka, Łukasz (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
According to the presented studies, the health condition of animals in rearing and breeding should be regularly monitored. This would allow early detection of delicate deviations in the body of clinically healthy individuals. Unfortunately, regular monitoring of the health of animals in commercial production is not performed. It follows that this type of research should be an introduction to further, more inquisitive steps. This can form the basis for further courses of action, indicating which organs or tissues field doctors or researchers should be interested in and what to pay attention to in order to find the correct answer, concerning the situation in the animal body. In the future, we should determine biomedical markers for use in precision veterinary medicine. In human medicine, this has been practiced with great success. The problem, however, is that we are getting to know more and more substances produced by mold fungi. This causes a build-up of new interpretative problems, causing health conditions (diagnosis), as well as analytical problems. To fully understand the results we need new techniques to assess toxicological and chemical hazards, including those related to undesirable substances. We need a solid knowledge of the biological pathways underlying the toxicity and tolerance to interference factors toxicological processes. We hope that the presented study will allow for a better understanding of mycotoxicoses that bother us and our animals, which will allow for more effective preventive actions.